Effectiveness of dragon fruit juice and red guava juice in increasing hemoglobin levels among pregnant women with anemia - Utin Agustin; Meinasari Kurnia Dewi; Retno Sugesti (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Anemia in pregnant women causes premature birth, prolonged labor due to uterine muscle fatigue in contracting (uterine inertia), postpartum hemorrhage due to the absence of uterine muscle contractions (uterine atony), shock, infection both during labor and postpartum, and severe anemia (<4 gr%) can cause cordis decompensation. Purpose: To analyze the effectiveness of giving dragon fruit juice and red guava juice to increase hemoglobin levels. Method: The method used is Quasi Experiment with the approach used, namely pre and posttest two groups. The sample in this study were 30 pregnant women in the first, second, and third trimesters with anemia. Sampling used a purposive sampling method, the measuring instrument used was an observation sheet. Results: This study found that the average hemoglobin level before administration of red guava juice was 10.367 g/dL, after administration of 12.300 g/dL, and the average hemoglobin level before administration of red guava juice was 10.187 g/dL, after administration of 11.640 g/dL. Red guava juice was more effective than dragon fruit juice in increasing hemoglobin levels in pregnant women with anemia with a p-value of 0.001 < 0.05 and a mean difference of 0.066. Conclusion: There is an effect of administering dragon fruit juice and red guava juice on increasing hemoglobin levels in pregnant women with anemia. Suggestion: It is recommended that community health centers and clinics develop non-pharmacological treatments for pregnant women, especially those with anemia.